2022
DOI: 10.1021/acs.macromol.1c02472
|View full text |Cite
|
Sign up to set email alerts
|

1,1,3,3-Tetramethylguanidine-Mediated Zwitterionic Ring-Opening Polymerization of Sarcosine-Derived N-Thiocarboxyanhydride toward Well-Defined Polysarcosine

Abstract: Zwitterionic ring-opening polymerization (ZROP) of sarcosine-derived N- thiocarboxyanhydrides (Me-NNTAs) can be induced by using 1,1,3,3-tetramethylguanidine (TMG) initiators in CH 2 Cl 2 at 25 °C, rapidly producing well-defined polysarcosine polymers with controlled molecular weights ( M n = 1.9–37 kg/mol) and narrow molecular weight distributions ( Đ = 1.01–1.12). The reaction exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…When a carboxylic acid/TMG (or carboxylic acid/benzylamine) mixture was used as the initiator, both the nucleophilic carboxylate and TMG (or benzylamine) possibly served as the initiator. Actually, polymers with TMG end group were indeed observed in the previously reported work if TMG alone was used as the initiator . Moreover, if the monomer was initiated by the carboxylate to form an anhydride end group which was replaced by the benzylamine through nucleophilic substitution, then a polymer with a carboxylate end group should be observed in the ROP with high concentration of AA (e.g., [M] 0 /[BnNH 2 ] 0 /[AA] 0 = 25:1:25) since the benzylamine should be in the salt form and unlikely to attack the anhydride.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…When a carboxylic acid/TMG (or carboxylic acid/benzylamine) mixture was used as the initiator, both the nucleophilic carboxylate and TMG (or benzylamine) possibly served as the initiator. Actually, polymers with TMG end group were indeed observed in the previously reported work if TMG alone was used as the initiator . Moreover, if the monomer was initiated by the carboxylate to form an anhydride end group which was replaced by the benzylamine through nucleophilic substitution, then a polymer with a carboxylate end group should be observed in the ROP with high concentration of AA (e.g., [M] 0 /[BnNH 2 ] 0 /[AA] 0 = 25:1:25) since the benzylamine should be in the salt form and unlikely to attack the anhydride.…”
Section: Resultsmentioning
confidence: 61%
“…Actually, polymers with TMG end group were indeed observed in the previously reported work if TMG alone was used as the initiator. 37 Moreover, if the monomer was initiated by the carboxylate to form an anhydride end group which was replaced by the benzylamine through nucleophilic substitution, then a polymer with a carboxylate end group should be observed in the ROP with high concentration of AA (e.g., [M] 0 /[BnNH 2 ] 0 /[AA] 0 = 25:1:25) since the benzylamine should be in the salt form and unlikely to attack the anhydride. In fact, only polymer with benzylamine end group was observed regardless of the concentration of AA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, there is minimal control over the chain ends of the polypeptoids using this strategy and molecular weight plateauing was still observed at high DPs. 1,1,3,3-Tetramethylguanidine (TMG) was used to initiate the ROP of methyl-NNTAs by Zhang and co-workers, producing well-defined polypeptoids with no plateauing observed for monomer to initiator ratios up to 400:1 and predictable chain ends (Figure B) . A novel peptoid synthetic method inspired by the controlled, living polymerization of NCAs with transition-metal catalysts was created by Kramer and Clauss to produce chain-length controlled polypeptoids with functionalized end groups (Figure B) .…”
Section: Optimizing the Solution-phase Synthesis Of Peptoidsmentioning
confidence: 99%
“…1,1,3,3-Tetramethylguanidine (TMG) was used to initiate the ROP of methyl-NNTAs by Zhang and co-workers, producing well-defined polypeptoids with no plateauing observed for monomer to initiator ratios up to 400:1 and predictable chain ends (Figure 3B). 82 A novel peptoid synthetic method inspired by the controlled, living polymerization of NCAs with transitionmetal catalysts was created by Kramer and Clauss to produce chain-length controlled polypeptoids with functionalized end groups (Figure 3B). 75 Using nickel amido-amidate preformed catalysts, the ROP of NNCAs yielded polypeptoids with excellent control over chain lengths for a variety of hydrophilic and hydrophobic side chains.…”
Section: Initiator Selectionmentioning
confidence: 99%
“…[ 51 ] A recent study, however, demonstrated that Me‐NTA can undergo zwitterionic ring‐opening polymerization (ZROP) in CH 2 Cl 2 at 25 °C using 1,1,3,3‐tetramethylguanidine (TMG) as the initiator to obtain well‐defined polysarcosine with controlled MW and narrow MW distribution. [ 52 ] The polymerization rate of Me‐NTA using the TMG initiator is nearly two‐fold faster than using the benzylamine initiator. This is attributed to the stable propagating macro‐zwitterion of positively charged guanidinium and negatively charged thiocarbamate ends.…”
Section: Synthesis Of Polypeptoids By Controlled Ring‐opening Polymer...mentioning
confidence: 99%